More than honor - Weber, David, 1952-; Drake, David, 1945-; Stirling, S. M. (Weber, David, 1952- Worlds of Honor, 2023)
In hardcover for the first time, first entry in the Worlds of Honor anthology series, by three giants of military SF. Honorverse short novels by Weber, David Drake, and S.M. Stirling. The first entry in the Worlds of Honor anthology series, featuring stories set in David Weber's New York TImes best-selling Honorverse. Featuring "A Grand Tour" by master of military SF David Drake; "A Whiff of Grapeshot" by best-selling author S.M. Stirling: and "A Beautiful Friendship" by David Weber, the novella that would later become the first entry in Weber's Star Kingdom series. Also includes Honor Harrington series essay "The Universe of Honor Harrington" by Weber.